Pengembangan Media Pembelajaran Online Interaktif Menggunakan Virtual Reality Video 3600 Pada Materi Sistem Tata Surya Kelas Vl Sekolah Dasar - Irdam Denni; Neli Rismayanti; Dudi Suprihadi; Aceng Ahmad Rodian Susila; Demmy Dharma Bhakti (Universitas Sebelas Maret, 2025)
Learning at SDN 4 Caringin still uses textbooks with lecture and discussion methods so that students have difficulty in understanding abstract material resulting in difficult and boring lessons. This researcher aims to develop interactive online learning media using Virtual Reality video 3600 for solar system material and test the feasibility of this learning media. The research method used is R&D with the ADDIE model. Media development was studied on sixth grade elementary school students at SDN Caringin 4 with the research method used is R&D (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of this media development obtained a value of 96% and 98% from media experts so that the media is suitable for use with revisions, the value from material experts obtained 98% so that the material is suitable for use without revision. The results of the learning media trial on students on a large scale obtained a value of 95% so it can be concluded that it is suitable for use as a learning media.Pembelajaran di sekolah SDN 4 Caringin masih menggunakan buku paket dengan metode ceramah dan diskusi sehingga peserta didik kesulitan dalam memahami materi yang bersifat abstrak mengakibatkan pelajaran sulit dipahami dan membosankan. Peneliti ini bertujuan untuk mengembangkan media pembelajaran online interaktif menggunakan Virtual Reality video 3600 untuk materi sistem tata surya dan menguji kelayakan dari media pembelajaran ini. Metode peneltian yang digunakan adalah R&D dengan model ADDIE. Pengembangan media diteliti kepada siswa Sekolah Dasar kelas VI di SDN Caringin 4 dengan Metode peneltian yang digunakan adalah R&D (Research and Development) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Hasil dari pengembangan media ini diperoleh nilai 96% dan 98% dari ahli media sehingga media layak digunakan dengan revisi, nilai dari ahli materi memperoleh 98% sehingga materi layak digunakan tanpa revisi. Hasil uji coba media pembelajaran terhadap peserta didik dengan skala besar mendapatkan nilai 95% sehingga dapat disimpulkan layak digunakan sebagai media pembelajaran.